Análise das oficinas de conservação e preservação em suporte de papel do Arquivo Público do Estado do Pará - MELO, Bruno Edilson da Silva (2022)
The present work aimed to describe and analyze the workshop on preservation and conservation of documents in paper support offered by the Public Archives of the State of Pará (APEP), which is part of the institutional Project Arquivo de Portas Abertas. Based on bibliographies on the subject of document preservation and conservation and on the answers obtained in the interviews and questionnaires applied with the institution's director, the facilitating server and the workshop participants, the steps, techniques and instruments used and their importance were identified. strategic in the agility of the process of preserving the documents held by the agency. It was also revealed the impacts generated by the workshop with its participants, concluding that its objective of training and improving professionals to work with handling documents in paper support is being achieved.